User Research Report : Summary for the development of the Data Portal “BIBB Occupations and Skills Radar” - Schnepf, Timo [Verfasser] (Bundesinstitut für Berufsbildung, 2025)
"This user research report serves as preliminary work for the development of the new data portal ”BIBB Occupations and Skills Radar” (“BIBB Berufe- und Kompetenzradar”, or short BKR) funded by the BMBF (Federal Ministry of Education and Research, duration 2022-2026). The report uses various sources to identify target group-specific user requirements. It is based on a quantitative survey of users of bibb.de (on-site survey), a survey of young adults, qualitative interviews with decision-makers and stakeholders from politics and vocational training practice, a literature review, an online traffic analysis of the BIBB publication directory (“Fachpublicationen”), an analysis of the BIBB database on request management (“Anfragenmanagement”), a market analysis, and internal discussions with managers. User requirements were derived from these sources and divided into “cross-user” and “user-specific” requirements in this report. The results show a heterogeneous picture of the BIBB's target groups, describe which statistics are of particular interest, and which challenges need to be taken into account when developing a new portal." (BIBB Autorenreferat)
Keywords: G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 1.1.4 Statistiken zu speziellen Problemlagen & Bereichen; S 6 Berufsbereiche; 370; Berufsbildungsforschung; Open Science; Massendaten; Berufsbildungsstatistik; Berufsstatistik; Datawarehouse; Datenbank; Anforderungsprofil; Befragung